VD_FINDINFO Jug / 2021 / 127 vom 7. Oktober 2020 - VD Tribunal cantonal (2020)
ESCROQUERIE, BAIL À LOYER, ASTUCE, INDEMNITÉEN GÉNÉRAL, FAUTE, FRAIS JUDICIAIRES | 41 CO, 146 CP, 426 al. 1 CPP (CH), 429 CPP (CH)